Legal Certainty in Carbon Trading in Indonesia - Tektona, Rahmadi Indra; M Adriani Harefa, Jemi; Yasa, I Wayan (Simbur Cahaya, 2024)
Global climate change has become one of the most important issues facing the world today. Climate change can be defined as long-term changes in temperature and weather conditions. The main cause of climate change is the increase in Greenhouse Gas (GHG) emissions into the atmosphere due to various human activities, including industrial and transportation activities. To combat climate change, the international community has developed various agreements and frameworks, including the Kyoto Protocol, followed by the Paris Agreement, which aim to reduce GHG emissions globally. One of the instruments developed to reduce GHG emissions is carbon trading, also known as emissions trading. Carbon trading is a mechanism where companies or countries can buy or sell permits to emit GHGs, known as carbon credits or emission units, with the goal of effectively reducing emissions. Through carbon trading, countries or companies can reduce GHG emissions, helping other countries achieve their emission targets more economically. Indonesia, as a country with high GHG emissions, has a responsibility to reduce emissions in accordance with international commitments such as the Paris Agreement. Although steps have been taken, such as the development of renewable energy, regulations. This research uses a normative juridical legal research method with a conceptual approach and a statute approach. This study will also discuss the role of financial institutions and capital markets in carbon trading in Indonesia, the carbon trading system in Indonesia, and the differences in carbon trading mechanisms between Indonesia and other countries.